Identification of Misconception in Basic Material of Evolution Theories at Biology Department Students of Padang State University - Atikah Fauziah; Rahmawati Darussyamsu; Rahmadhani Fitri (Bioeducation Journal, 2019)
Evolution as a subject in lecture is a material that has many concepts, theoretical, and hard to understand. Then it impacts some misconception on students. Misconception is a situation where the concept that students’ get is different from what experts' mean. The purpose of this research is to know the evaluations' concepts that be misconception by biology' students of Padang state University who has been learning evolution subject and to know the percentage of misconception which had been happened. This research is a desriptive study. Subject of this research is the students of biology of Padang state University who has been learning evolution in second semester in academic year 2016/2017. Sample of this research is all subject that still active in college. Variable of this research is students' misconception toward concpets in evolution material. Instrument of this research is multiple choice test that be equipped with criteria of certainty of response index (CRI) have the form of numeral 1, 2 and 3 which be choosed based on level of conviction of the answer. Analysis of the data used quantitative with count percentage of students have misconception that is students who are choosen flase answer ans index 3 in CRI. Based on data analysis indicate students of biology of Padang University did misconception in evolution material after learning evolution subject with high percentage be found in basic material about definition and the scope of evolution is 39.52% and the low percentage of misconception be found in basic material about Darwin's evolution is 15.86%.